Economic Structure and Welfare Indicator Changes in West Kalimantan after Oil Palm Expansion - Sudrajat, Jajat (Jurnal Ekonomi Kuantitatif Terapan; 2019: Vol. 12, No.1, Februari 2019 (pp. 1-107)DO - 10.24843/JEKT.2019.v12.i01.p09, 2019)
This study aimed to analyze the economic structure changes of regencies and cities in West Kalimantan after a massive expansion of oil palm plantations, to analyze the economic sectors that have competitive advantages, and to analyze the impact of various changes on social welfare. The study was conducted by collecting data about employment and some welfare indicators at the statistic central bureau. Data were analyzed by using the shift-and-share and also descriptive method. This study concludes that regional autonomy and oil palm expansion policy have a positive impact on economic structure changes either in regencies or Pontianak. The economic sectors that have a competitive advantage in the regencies are agriculture, electric/gas/water, transport and communication, trade/hotel/restaurant, and services. Meanwhile, in Pontianak, there are agriculture, transport and communication, manufacturing industry, and electric/gas/water sectors. Economic structure changes also show positive impacts on social welfare. It is marked by the decline of poverty rate in Pontianak and the province as a whole. In addition, it is also signalled by the improvement of Human Development Index (HDI) and Gross Regional Domestic Product (GRDP) per capita in the regencies, Pontianak, and the province. Meanwhile, its impact toward poverty reduction in regency level does not show significant results yet.